Мотивационная составляющая при внедрении систем бюджетирования - Недбайло, Д.Е.; Ширай, О.С. (Культура народов Причерноморья, 2013)
В статье освещены вопросы мотивации персонала при внедрении систем
бюджетирования. Процесс внедрения систем бюджетирования на предприятиях часто
сопровождается активным сопротивлением персонала, которое возникает вследствие
недоинформированности сотрудников предприятия о готовящихся изменениях в их работе и
обязанностях, а так же из-за отсутствия у работников четкого представления взаимосвязи между
успехом внедрения проекта системы бюджетирования и вознаграждением.
В статье рассмотрены следующие виды мотивации: экономическая, социальная, моральная и схемы их
применения.
Ключевые слова: бюджетирование, персонал, мотивация, сопротивление персонала, приростное
бюджетирование, экономическая мотивація. В статті висвітлені питання мотивації персоналу при впровадженні систем
бюджетування. Процес впровадження систем бюджетування на підприємствах часто
супроводжується активним опором персоналу, що відбувається через недоінформованість працівників
про майбутні зміни в їх роботі і обов'язках, а також через відсутність у працівників чіткого уявлення
взаємозв'язку між успіхом впровадження системи бюджетування та винагородою. Ця стаття описує
наступні види мотивації: економічна, соціальна, моральна і схеми їх застосування.
Ключові слова: бюджетування, персонал, мотивація, опор персоналу,приростне бюджетування,
економічна мотивація. The article highlights the issues of employee motivation in the implementation of budgeting. The
implementation process of budgeting systems in enterprises is often accompanied by the resistance of the staff,
which is caused by ignorance of the company's employees about upcoming changes in their work and
responsibilities, as well as due to the lack of a clear view of employees relationship between the success of the
implementation of the project-based budgeting and reward.
Determined the importance of the head of any skill level to link business objectives with labor motivation of staff.
The paper considers the following types of motivation: economic, social, moral and schemes of their application.
The article also gives the characteristic qualities of the personnel needed to implement the goals of the company,
in particular the introduction of the system of budgeting. The author describes the main causes of resistance to
the introduction of the staff of the budgeting system in the enterprise, such as the lack of information and lack of
motivation.
Explored motifs that contribute to the urge staff to take an active part in the implementation of system of
budgeting. For the successful implementation of the budgeting system in the enterprise to conduct motivational
policies of personnel directly engaged in it.
Keywords: Budgeting, personnel, motivation, staff resistance.